Penerapan Peraturan Daerah Kota Tasikmalaya Nomor 12 Tahun 2009 Dalam Membangun Kehidupan Masyarakat Berlandaskan Ajaran Islam - Safitri, Annida; R, Rudiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Regional Regulation (Perda) of Tasikmalaya City Number 12 of 2009 concerning the Development of Community Life Values Based on Islamic Teachings and Social Norms is a strategic effort to create a harmonious, religious, and Islamic value-based social order. This regulation stems from Tasikmalaya's identity as a